PERAN KOMUNIKASI KELUARGA DALAM PENYIAPAN KEHIDUPAN BERKELUARGA BAGI REMAJA UNTUK MENCEGAH MASLAH GIZI PADA BALITA(STUNTING) - Adi, Fajar; Solihin, Olih (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2022)
he family development program is one part of the Bangga Kencana Program, implemented as an effort to realize quality families living in a healthy environment. Adolescents as a bride-to-be become the focus of family development and stunting programs need to be prepared to live a family life in an effort to prevent stunting. This study aims to analyze the role of family communication and the efforts that have been made in family life preparation for adolescents to prevent stunting. This study uses a qualitative approach using content analysis techniques towards available documents. Findings on the role of family communication in family life preparation for adolescents to prevent stunting are very important for family development through the role of the family as a communication system and the role of parents in building intimate relationships with family members. So it is recommended to apply a family communication approach in family life preparation for adolescents to prevent stunting, by emphasizing the role of the family as a communication system. This study has limitations on the number of documents in the content analysis, so for further study it is recommended to increase the number of documents.